2018
DOI: 10.4187/respcare.06436
|View full text |Cite
|
Sign up to set email alerts
|

Objective Versus Self-Reported Adherence to Airway Clearance Therapy in Cystic Fibrosis

Abstract: BACKGROUND: Historically, studies of adherence to airway clearance therapy in cystic fibrosis (CF) have relied on self-reporting. We compared self-reported airway clearance therapy adherence to actual usage data from home high-frequency chest wall compressions (HFCWC) vests and identified factors associated with overestimation of adherence in self-reports. METHODS: Pediatric patients who perform airway clearance therapy with a HFCWC vest were eligible to participate. Objective adherence data were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Adherence to all aspects of the CF daily regimen, including airway clearance therapy and dietary recommendations, has been studied using various methods. [1][2][3][4] Indeed, a significant disparity between self-reported and objectively measured adherence exists, 5 rendering assessment of adherence and comparison between different studies rather challenging. 6 Respiratory disease accounts for most deaths in CF, 7 and inhaled medication is used to reduce exacerbations and improve lung function and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to all aspects of the CF daily regimen, including airway clearance therapy and dietary recommendations, has been studied using various methods. [1][2][3][4] Indeed, a significant disparity between self-reported and objectively measured adherence exists, 5 rendering assessment of adherence and comparison between different studies rather challenging. 6 Respiratory disease accounts for most deaths in CF, 7 and inhaled medication is used to reduce exacerbations and improve lung function and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, previous literature in other self-report versus objective measurement conditions would make this possibility unlikely. 26 27 The LVR counter used in this project is an in-house-developed prototype and as such does not provide a clear pathway to commercial and clinical translation of our findings; however, we suggest that this paper illustrates clear translational opportunities. Clinically, objective data provide opportunities for home monitoring of therapy, may suggest poor usage and may prompt clinicians to identify barriers to treatment, and similarly, patterns of use may provide important information about users’ beliefs and treatment choices, both positive and negative.…”
Section: Discussionmentioning
confidence: 82%
“…Greater discordance in the direction of the diary suggests overestimation of self-reported LVR usage, a common finding in other chronic conditions when self-report measures have been compared with objective measures of use. 26 27 In one study, 47% of people with cystic fibrosis reported performing more airway clearance therapy sessions than objectively recorded data would suggest across a 5-week period. 26 In contrast, medication adherence literature would indicate better concordance, with 72% of studies reporting ‘high’ concordance; high concordance is defined as <10% difference between self-reported diary and other measures of adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations